(untitled) (Journal of Academic Research, 2024)
Anemia in pregnancy is considered a major public health problem and is commonly associated with many consequences as low birth weight, premature delivery and the increased risk of the maternal mortality and morbidity in the pregnant women, mainly in the developing countries. The present study was designed to estimate the changes in hematological parameters in women during pregnancy at EL-Bayda city. Cross sectional study involved 350 randomly selected pregnant mothers who are attended several medical clinics in the period of February to July 2022, of age group (17-48) years. A venous blood samples were collected in EDTA tubes and analyzed for complete blood counts (CBC) to evaluate hemoglobin levels (Hb), mean cell hemoglobin (MCV), mean cell hemoglobin (MCH), mean cell hemoglobin concentration (MCHC), white blood cells (WBCs) and platelets count. Other data were also reported including women age, trimester of pregnancy, the number of the gravida and the parity. Results will be analyzed by SPSS version 26 and represented as mean ± SE and P value is considered significant when it is less than 0.05. The mean age of the participants women was 29.5(±0.33), the overall prevalence of anemia was 57% and vast of them were in third trimester period. Out of 198 anemic women.